2021
DOI: 10.1037/edu0000488
|View full text |Cite
|
Sign up to set email alerts
|

How students’ perceptions of teaching quality in one subject are impacted by the grades they receive in another subject: Dimensional comparisons in student evaluations of teaching quality.

Abstract: According to dimensional comparison theory (DCT), students evaluate their ability in one domain (e.g., math) by comparing their achievement in that domain with their achievement in other domains (e.g., English). Primarily in research on students' academic self-concept, these comparison processes have been found to lead to positive associations within subjects (e.g., the better the student's achievement in math, the higher that student's math self-concept) but negative associations between subjects (e.g., bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…The present study was part of a larger research project about the validity of students' teaching quality for predicting learning (Teaching Quality From the Students' Perspective, UNITAS; Jaekel et al 2021) which was approved by the Ministry of Culture, Youth, and Sport of Baden-Württemberg. In addition, the ethics committee of Economics and Social Sciences at the University of Tübingen confirmed that the procedures were in line with the ethical standards for research with human subjects (File number A2.5.4-074_aa).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was part of a larger research project about the validity of students' teaching quality for predicting learning (Teaching Quality From the Students' Perspective, UNITAS; Jaekel et al 2021) which was approved by the Ministry of Culture, Youth, and Sport of Baden-Württemberg. In addition, the ethics committee of Economics and Social Sciences at the University of Tübingen confirmed that the procedures were in line with the ethical standards for research with human subjects (File number A2.5.4-074_aa).…”
Section: Methodsmentioning
confidence: 99%
“…Each dimension was assessed with three to four items, for a total of 21 items (Supplemental Table S1, available in the online version of this article). The items from the student and parent perspectives had the same general wording, for example, “My math teacher always knew exactly what I was working on” and “The math teacher always knew exactly what my child was working on.” Most of the items had previously been used in large-scale studies, such as PISA or TIMSS (Aditomo & Köhler, 2020; Jaekel et al, 2021; Kunter & Baumert, 2006; Lüdtke et al, 2006). Additionally, we adapted the specific subject named in the items to address each of the three subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Although the construct‐generalized I/E model allows for examining effects of dimensional comparisons between virtually all domain‐specific constructs, most researchers to date have used this model to examine effects of dimensional comparisons between achievements. For example, researchers have regressed domain‐specific values (Jansen et al., 2021), motivation (Marsh, Abduljabbar, et al., 2015), enjoyment (Götz et al., 2008), test anxiety (Arens et al., 2017), achievement goals (Dörendahl et al., 2021), perceptions of teaching quality (Jaekel et al., 2021), or educational choice decisions (Van Keyserlingk et al., 2021) on students' domain‐specific achievements and found indications of dimensional comparison effects on these constructs (although these were partly mediated by students' self‐concepts). Other studies found indications of dimensional comparison effects by regressing self‐concepts in different sports disciplines (Lohbeck et al., 2021), subjects in the study of psychology (Wolff, Helm, Preckel, et al, 2018), or areas of professional knowledge relevant for teachers (Paulick et al., 2017) on achievements in these domains, or by regressing students' domain‐specific collective self‐concepts (relating to the perceived ability of their class) on the average achievements of their class (Wolff, Lüdtke, et al., 2021).…”
Section: Dimensional Comparison Effectsmentioning
confidence: 99%
“…In order to do so, however, we need to learn much more about the mental models that underlie students' ratings and the extent to which these models differ from those of adult observers evaluating teaching quality. A recent study by Jaekel et al, (2021) found that student ratings of teaching quality in one school subject (mathematics or German language) did not only result from students' daily experiences in the subject at hand, but were also affected by their experiences in the respective other subjects. Students seem to make use of comparative information when objective criteria for good teaching is not available.…”
Section: The Idiosyncratic Nature Of Student Ratingsmentioning
confidence: 99%